The Impact of Economic Factors on the Emergence and Development of Organized Crime - Stevanović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
In this paper, the author speaks about the key aspects of the economic impact on the emergence and development of organized crime. The basic hypothesis of the authors of criminality explained by economic factors is that the commission of crimes is caused by economic deprivation of individuals and collectives, which is often considered a consequence of the poor state of the economy and high unemployment in a society, as a systematic generator of criminal acts aimed at achieving illegal profits. It was stated that social conditions, particularly economic, are not only important for the decision of a certain group of people to act as an organized criminal group that can be denoted as the initial moment, but have decisive influence on where, when and how the individual acts that are traditionally considered activities organized crime such as drug trafficking, arms smuggling, money laundering etc., can be carried out most effectively and fruitfully. It is a historical fact that the economic situation of a number of people exists in every economic framework and the period of socio-economic order. Individuals are eventually began to associate would not be resisted redistribution of material resources which they had been imposed, and that they considered unjust.